(untitled) (Journal of The Colloquium for Information Systems Security Education, 2020)
In this work, we consider the nexus between blockchain technology and computer science curriculum. While it is possible to introduce the blockchain paradigm using a single course, the depth of a single topic can often be sacrificed at the expense of covering a breadth of information. As blockchain is an emerging technology, it is important to embed various concepts throughout the undergraduate curriculum with the depth necessary to reinforce each facet. Using a just in time approach, we define exactly where and how blockchain topics relevant to computer science should be introduced. As a means for active learning pedagogy, we introduce a lab framework for students to gain hands-on experience. Finally, we describe collaborations with industry to provide mentorship and internship opportunities.